Exosome-delivered NR2F1-AS1 and NR2F1 drive phenotypic transition from dormancy to proliferation in treatment-resistant prostate cancer via stabilizing hormonal receptors - Wenbin Chen; Yiyou Mao; YiYuan Zhan; Wenfeng Li; Jun Wu; Xiangming Mao; Bin Xu; Fangpeng Shu (Journal of Nanobiotechnology)
Abstract Cancer cells acquire the ability to reprogram their phenotype in response to targeted therapies, yet the transition from dormancy to proliferation in drug-resistant cancers remains poorly understood. In prostate cancer, we utilized high-plasticity mouse models and enzalutamide-resistant (ENZ-R) cellular models to elucidate NR2F1 as a key factor in lineage transition and ENZ resistance. Depletion of NR2F1 drives ENZ-R cells into a relative dormancy state, characterized by reduced proliferation and heightened drug resistance, while NR2F1 overexpression yields contrasting outcomes. Transcriptional sequencing analysis of NR2F1-silenced prostate cancer cells and tissues from the Cancer Genome Atlas-prostate cancer and SU2C cohorts indicated exosomes as the most enriched cell component, with pathways implicated in steroid hormone biosynthesis and drug metabolism. Moreover, NR2F1-AS1 forms a complex with SRSF1 to upregulate NR2F1 expression, facilitating its binding with ESR1 to sustain hormonal receptor expression and enhance proliferation in ENZ-R cells. Furthermore, HnRNPA2B1 interacts with NR2F1 and NR2F1-AS1, assisting their packaging into exosomes, wherein exosomal NR2F1 and NR2F1-AS1 promote the proliferation of dormant ENZ-R cells. Our works offer novel insights into the reawaking of dormant drug-resistant cancer cells governed by NR2F1 upregulation triggered by exosome-derived NR2F1-AS1 and NR2F1, suggesting therapeutic potential for phenotype reversal. Graphical Abstract